Government decentralization as a disincentive for transnational terror? : an empirical analysis - Axel Dreher; Justina A. V. Fischer (Center for Economic Studies and ifo Institute (CESifo), 2009)
Using panel data for a maximum of 109 countries over the years 1976-2000, we empirically analyze the impact of decentralization on the occurrence of transnational terror. Our results show that expenditure decentralization reduces the number of transnational terror events in a country, while political decentralization has no impact. These results are robust to the choice of control variables and method of estimation.
Keywords: D74; H70; H40; 330; terrorism; decentralization; federalism; governance quality; government effectiveness; Dezentralisierung; Finanzföderalismus; Regierung; Politische Gewalt; Welt